2014
DOI: 10.1093/ejcts/ezu324
|View full text |Cite
|
Sign up to set email alerts
|

Pain and recovery are comparable after either uniportal or multiport video-assisted thoracoscopic lobectomy: an observation study

Abstract: Uniportal VATS lobectomy is safe, and there is no appreciable negative impact on the hospital stay or morbidity. Patient-reported pain and morphine use in the first 24 h was low with either technique. Larger prospective studies are needed to quantify any benefit to a particular approach for VATS lobectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 21 publications
3
58
1
Order By: Relevance
“…They concluded that uniportal VATS lobectomy does not present better postoperative outcomes (postoperative pain, delay in removing the paravertebral catheter and the chest drain, the duration of postoperative hospital stay, postoperative complications and the operative or 30-day mortality) than other VATS lobectomy techniques. These conclusions confirm the results previously described by McElnay et al (11) whose observational study demonstrated once again the feasibility of the procedure, but did not find differences in terms of pain or recovery between SP-VATS and VATS.…”
Section: A Greater Quality Of Clinical Evidence Is Neededsupporting
confidence: 92%
“…They concluded that uniportal VATS lobectomy does not present better postoperative outcomes (postoperative pain, delay in removing the paravertebral catheter and the chest drain, the duration of postoperative hospital stay, postoperative complications and the operative or 30-day mortality) than other VATS lobectomy techniques. These conclusions confirm the results previously described by McElnay et al (11) whose observational study demonstrated once again the feasibility of the procedure, but did not find differences in terms of pain or recovery between SP-VATS and VATS.…”
Section: A Greater Quality Of Clinical Evidence Is Neededsupporting
confidence: 92%
“…Results of performing this procedure can be found in other articles in this issue and elsewhere in the literature (5,6). It must be acknowledged that at the time of this writing, there is very little clinical data showing a significant clinical advantage for uniportal VATS when performing lobectomy (19,20). However, there is sufficient evidence that the approach is safe (5,(12)(13)(14)19,20).…”
Section: Commentsmentioning
confidence: 99%
“…It must be acknowledged that at the time of this writing, there is very little clinical data showing a significant clinical advantage for uniportal VATS when performing lobectomy (19,20). However, there is sufficient evidence that the approach is safe (5,(12)(13)(14)19,20). This means that VATS surgeons can safely learn and practice uniportal lobectomy, hopefully accumulating the clinical evidence that will ultimately show the real benefits of uniportal VATS in our specialty.…”
Section: Commentsmentioning
confidence: 99%
“…Though a recent randomized study attempted to address this issue, there was considerable variation in methodology, particularly in the surgical technique used (10). Another observational study failed to show an appreciable difference in pain when comparing uniportal lobectomy to standard VATS technique, though the study was done as a non-inferiority report and included only 15 patients in the uniportal arm (11).…”
Section: Introductionmentioning
confidence: 99%